Studi Komparatif Komprehensif Sistem Ekonomi Islam, Kapitalis dan Sosialis - Abdurrahman (Institut Agama Islam Sahid Bogor, 2021)
In the midst of the growing trend of Islamic economics, it is necessary to have an in-depth study of this system. Is it true that it is just a religious norm? Or just following a spiritual trend that has recently been on the rise.Indeed, the Islamic economic system is different from other economic systems, it is not the result of the adoption of a socialist system that fights for pseudo-equality rights. It is also very different from the capitalist system which gives property rights to individuals freely. The Islamic economic system is a system based on divine values ​​and built on general principles for the implementation of all economic activities.The capitalist economic system is based on the freedom of individuals to own various wealth on this earth without any restrictions, this has an effect on the inequality of the social system, the rich getting richer and the poor getting poorer. In addition, various social problems appeared, such as the landlords and slaves, the end of this system was the revolt of the workers who demanded their rights as human beings. If the capitalist system protects the interests of the bourgeoisie, the socialist system fights for equal rights for all citizens. The similarity they want is equality in all rights and eliminating ownership rights to a material object. In this case, every individual is not allowed to have material rights except those that are his necessities of life. All economic systems are governed by the State. In this system, it seems that they are defending the workers, but in essence this system is a protector for leaders and dignitaries to exploit the wealth of the people.The Islamic economic system has methods and principles that are different from other economic systems, it gives ownership rights to an object, but there are standard rules so that wealth is not only among the rich. The mechanism used is the existence of zakat law. Some of the wealth that is needed by the people is managed by the state and may not be owned by individuals. From here, the Islamic economic system becomes a comprehensive economic system and will suitably be applied anytime and anywhere.